POLARIMETRIC CALIBRATION OF THE SPACEBORNE DIRECTIONAL POLARIMETRIC CAMERA INSTALLED ON THE GF-5 SATELLITE - Y. Yuan; Z. Liu; Z. Liu; X. Zheng; Q. Kang; H. Wu; J. Li; S. Li; D. Luo; J. Hong (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
The Spaceborne Directional Polarimetric Camera (SDPC) is dedicated to obtain an accurate information of clouds and microphysical properties of aerosol particles via multi-angle, multi-spectral and multi-polarization observations. It images the Earth with 110° field of view (FOV) in 3 polarimetric spectral bands and 5 non-polarimetric spectral bands from visible to near infrared. Due to its wide FOV telecentric optical system and multi-channels, polarization sensitivity of optical components (PSOC) and non-uniform response of pixels (NURP) are the main uncertainty factors of polarimetric calibration. In this paper, a polarimetric calibration model of SDPC has been constructed for increasing the measurement accuracy. Combined an integrating sphere with a polarization generator as source, PSOC can be measured in high accuracy by using the Fourier series analysis method which reduces the impact form the alignment error of the generator. The sectional viewing field measurement method is used to acquire NURP while the large aperture integrating sphere served as reference source. Subsequently, the data of NURP have been corrected by the relative transmittance of high frequency and low frequency respectively for polarized channels. The result of validation experiment shows that the polarization measurement errors in 0°, 15°, 30°, and 45° half field of view (HFOV) are all less than 0.5% when the degree of linear polarization of reference source is larger than 0.1.